Paradigma Pendidikan Islam dalam Teori Belajar: Analisis Brhavioristik, Kognitif, Humanistik, dan Konstruktivistik - Malida Nur Izzatul Mursyidah; Mu'alimin Mu'alimin; Mukaffan Mukaffan (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
The paradigm of Islamic education requires the integration of Western learning theories with an Islamic perspective to create a holistic approach to education. With the rapid development of psychological theories in education, such as behaviorism, cognition, humanism, and constructivism, it is essential to examine their relevance within the context of Islamic education. This article aims to analyze the integration of these theories in Islamic learning, with a focus on their connection to key Islamic concepts such as reward-punishment (pahala-dosa), reflection (tafakkur), self-actualization, mutual assistance (ta'awun), and consultation (syura). This study uses a literature review method with a qualitative approach. Articles were gathered through Google Scholar and Publish or Perish with keywords "Behaviorism in Islamic Education" AND "Cognitive Learning in Islam" AND "Humanistic Approach in Islamic Education" AND "Constructivism in Islamic Education." Of the initial 40 articles obtained, a screening process resulted in 5 articles that met the publication criteria (2020–2025), relevance to the topic, and open access. The review results show that integrating these theories into Islamic education can enrich the learning process by linking moral, social, and spiritual elements that are essential in Islamic teachings. This literature synthesis reveals the importance of integrating psychological theories with the principles of Islamic education to create a more comprehensive and holistic educational system. Further research should develop empirical methodologies and more detailed and practical application models in Islamic education practice.